The relation between peri-implantitis and metal release from implant material and prosthetic components. A TXRF answer - Grenón, Miriam Silvina (2019)
Fil: Grenón, Miriam Silvina . Universidad Nacional de Córdoba. Facultad de Odontología. Cátedra de Periodoncia A; Argentina.